Hubungan Terpaan Talk Show "Dr Oz" Di Trans Tv DenganGaya Hidup Sehat Pada Mahasiswa Komunikasi Angkatan Tahun 2013 Dan 2014(Studi Korelasi Pada Mahasiswa Ilmu Komunikasi Universitas Muhammadiyah Surakarta 2013 Dan 2014 ) - Nugraha, Paundra Arsa Dewa; , Agus Triyono, S.Sos, M.Si; , Budi Santoso, M.Si (2016)
This study took the title "Hubungan Terpaan Talk Show "Dr OZ In the Trans Tv with a healthy lifestyle in college students communication 2013 and 2014. The purpose of this research is to know the relationship between Terpaan Talk Show "Dr OZ" In the Trans Tv with a healthy lifestyle in college students communication 2013 and 2014. This study is a quantitative research and researchers using a method proporsional sampling. Namely with categorize members of the samples and science communication force faculty this group the faculty communication science force years 2013 and 2014. Based on testing of regressing doubled linear obtained equation Y = 2,377 + 0,743 X1 + 0,563 X2 + 0,454X3 + 0,367X4 + 0,612X5, with the coefficient of re gression indicator presenter of 0,743, indicator theme or the material event of 0,563, time variable the present of 0,454, indicator frequency show of 0,367 and indicator setting event of 0,612. This proves there is a significant between terpaan talk show "Dr Oz" In the Trans Tv with a healthy lifestyle in college students communication 2013 and 2014. This suggests that no significant influence dimensions Terpaan talk show "Dr OZ" In the Trans Tv (Is simultaneously) which includes the presenter, themes or the material event, hours running the frequency running and setting event against the student lifestyle in University Muhammadiyah Surakarta proven truth.